PENGALAMAN PERAWAT DALAM PENANGANAN PASIEN COVID-19 : TINJAUAN PUSTAKA - Roulita Roulita; Yanny Trisyani; Etika Emiliyawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Since the Covid-19 pandemic was announced by the world health organization (WHO) on January 30, 2020 until July 2021, the world's pandemic conditions have not subsided but have continued to increase, and even tripled. This spike is thought to be due to transmission from the Delta variant, where the number of patients who died from Covid-19 totaled 90,552 people, with a daily death toll of 1,893. (Ministry of Health, Republic of Indonesia). With the high number of Covid-19 cases, of course the workload of nurses has increased, and many have even fallen ill and died. This study aims to explore or review literature related to the experience of nurses in handling Covid-19 patients at the forefront. Article searches were carried out in digital online databases, Pubmed, EBSCO, Google Scolar, and Science Direct with the keywords 'Stress life or experience life', 'nurse', 'Covid-19 in emergency room'. Then the articles are selected according to the inclusion criteria, namely: The articles used are articles with the year of publication from January 2020 to July 2021, The language used in the article is English. The article used is an article with full text in pdf format, the theme of the article is the life experience of frontline nurses/IGD nurses in dealing with Covid-19 patients. Finally, 10 articles were analyzed in this literature review.